Evaluation of different organic and inorganic fertilizer combinations on the growth and yield of cabbage - Aryal, Dipak; Tamang, Asmita; Gharti Magar, Rishikesh (Future Science, 2024)
abbage (Brassica oleracea var. capitata) is the most important winter leafy vegetable in the world and belongs to the Cruciferae family. An experiment was conducted at the Horticultural farm of Gauradaha Agriculture Campus, Tribhuwan University, Jhapa, Nepal from 26th December 2022 to 2nd April 2023 to evaluate the different organic and inorganic fertilizer combinations on the growth and yield of cabbage (Brassica oleracea var. capitata L. cv. Green coronet). The experiment was conducted as a randomized block design with 7 treatments replicated 3 times and the treatments are T1: 25-ton FYM/ha, T2: 25-ton PM/ha, T3: 25-ton FYM/ha + NPK (RDF), T4: 25-ton PM/ha + NPK (RDF), T5: 20-ton FYM/ha + 10-ton PM/ha + NPK (RDF), T6: 10-ton FYM/ha + 20-ton PM/ha + NPK (RDF) and T7: control. Significant variation was found among the treatments. The result showed treatment had a significant role in different parameters. T3- The highest number of leaves, T5- the highest (leaf area, weight with roots, net head yield, horizontal head diameter), T4-highest (plant height, gross yield), T6- highest (stem girth, vertical head diameter) was obtained. On the result basis T5 (20-ton FYM/ha + 10-ton PM/ha + NPK (RDF) can be adopted as sustainable crop production. This study not only provides valuable insights into optimizing cabbage production but also underscores the importance of tailored fertilizer combinations for sustainable agriculture. Furthermore, the findings contribute to the broader discourse on enhancing crop yield while minimizing environmental impact. By elucidating the efficacy of specific fertilizer blends, this research paves the way for more efficient and eco-friendly farming practices, thereby promoting food security and environmental sustainability on a global scale.